PELATIHAN TEKNOLOGI PENERANGAN JALAN UMUM BERBASIS TENAGA SURYA DI DESA BENAN, KABUPATEN LINGGA, KEPULAUAN RIAU - Hollanda Arief Kusuma; Tonny Suhendra; Anton Hekso Yunianto (LPPM Universitas Andalas, 2023)
Pulau Benan, located in the Lingga Regency of the Riau Islands, is one of the emerging marine tourism destinations in Indonesia. However, achieving sustainable tourism development on the island necessitates an approach that encompasses economic, environmental, socio-cultural, and technological aspects. The development of appropriate technology products that can address local issues becomes critically important in this endeavor. A community engagement initiative took place from April to November 2021 on Pulau Benan, with a primary focus on assisting and improving solar-powered lighting systems. This initiative was spearheaded by faculty members from the Electrical Engineering Program at the Faculty of Engineering, Raja Ali Haji Maritime University. The goal of this endeavor was to enhance access to electricity on the island, which would bring significant benefits to the local population and support the sustainable growth of the tourism sector. The assistance provided in improving solar-powered lighting systems is not merely a step towards more sustainable energy use; it also enhances the quality of life for the island's residents. With a more reliable electrical infrastructure, the local community will have greater opportunities to develop businesses and contribute to the growth of the tourism sector on Pulau Benan. This initiative has not only created a positive impact at the local level but has also contributed to the national-level development of tourism. It is hoped that through the development of appropriate technology, Pulau Benan will serve as an exemplary model for other tourist destinations in implementing a comprehensive approach to sustainability.